Business Management of Indonesian Fintech amid covid-19 - Irawan, Irawan; Ferdyansyah, M. Syaf; Tamara, Dewi; Furinto, Asnan (ExcelingTech, 2020)
Abstract This paper examines the readiness of P2P Fintech in pandemic era. This paper follows business continuity models from BCG, Bain Company, and Deloitte. We combine three frameworks and identified three variables (respond/protect, recover, and Thrive/Retool) within dimension of Flatten Fight (during covid-19) and Future (after covid-19). We gathered 30 persons, from manager and director level of P2P Fintech. We distributed a questionnaire and analysed the data using SPSS for frequencies and means difference analysis. Then we interview the three (3) directors of P2P Fintech Company to reconfirm. We conclude that P2P Fintech is ready to do business continuation.